2015
DOI: 10.1016/j.ijme.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Contributing to a graduate-centred understanding of work readiness: An exploratory study of Australian undergraduate students' perceptions of their employability

Abstract: a b s t r a c tThe view that university graduates should be equipped with work-readiness skills has become increasingly normalised in university graduate capabilities designs. The framework of this study is established around an Australian university's graduate capabilities. This exploratory case study aims to contribute to a graduate-centred understanding of work-readiness. A qualitative methodology was used to map students' perceptions and evaluations of their skill development in criteria referenced graduat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
84
1
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 14 publications
0
84
1
5
Order By: Relevance
“…Even with the ever-evolving tertiary education landscape in the online environment across different university contexts and disciplines, it is apparent that students have an ongoing desire to learn and develop practical skills -an area that students often feel is underrepresented through their degree outside practical work experience opportunities (Cavanagh, Burston, Southcombe, & Bartram, 2015). While the links between unit content, assessment and discipline specific knowledge is clearer in some disciplines than others, student feedback suggests that, as a whole, they often see theory and practice as separate rather than interrelated and interwoven elements.…”
Section: Transferability To "Real World" Contextsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even with the ever-evolving tertiary education landscape in the online environment across different university contexts and disciplines, it is apparent that students have an ongoing desire to learn and develop practical skills -an area that students often feel is underrepresented through their degree outside practical work experience opportunities (Cavanagh, Burston, Southcombe, & Bartram, 2015). While the links between unit content, assessment and discipline specific knowledge is clearer in some disciplines than others, student feedback suggests that, as a whole, they often see theory and practice as separate rather than interrelated and interwoven elements.…”
Section: Transferability To "Real World" Contextsmentioning
confidence: 99%
“…Even though a facilitator may incorporate a range of activities and learning experiences that explores unit content in a variety of ways, explicitly indicating the real-world links and articulating how specific industry skills are being developed through the activities and making those connections clearer for the students aids in demonstrating relevance of the content and increasing student engagement (Cavanagh et al, 2015). Incorporating flexibility within learning environments allows discussions to evolve when deconstructing content and a number of ways to explore the subject matter to develop while also fostering the sense of community and building relationships.…”
Section: Transferability To "Real World" Contextsmentioning
confidence: 99%
“…In South Africa, Raftopoulos, Coetzee, and Visser (2009) found that oral and written communication skills, self‐discipline, time management, interpersonal skills, teamwork, problem‐solving skills, and a positive work ethic were important skills for securing employment. In Australia, higher order thinking, creativity, problem‐solving, and collaborative teamwork were the most problematic domains of skills development and competence in undergraduates' perceptions of their employability (Cavanagh, Burston, Southcombe, & Bartram, 2015). Furthermore, studies of health care professionals reinforce the concept that work readiness comprises multiple nondisciplinary dimensions, such as organizational acumen, clinical competence, and social intelligence, that can predict job satisfaction and work engagement (Walker & Campbell, 2013; Walker et al, 2013).…”
Section: Work Readinessmentioning
confidence: 99%
“…Growing evidence suggests that work readiness is an important global construct with implications for secondary and higher education in industrialized countries (Cavanagh et al, 2015; Gazibara et al, 2015; Raftopoulos et al, 2009). Creating opportunities for students to learn about themselves, their strengths and weaknesses, and their skill sets may increase work readiness.…”
Section: Work Readinessmentioning
confidence: 99%
“…Employability is affected by many factors such as professional identity, educational qualifications, labor markets and conditions, opportunities offered by employers (Rothwell & Arnold, 2007). According to Cavanagh, Burston, Southcombe, & Bartram (2015), work-readiness is illustrated in skills of writing, speaking, inquiry/research, critical thinking, creative problem solving and team work.…”
Section: Literature Review Context Of Employability Research In Vietnammentioning
confidence: 99%